Printed Wide-Slot Antenna Design with Bandwidth and Gain Enhancement on Low-Cost Substrate - M. Samsuzzaman; M. T. Islam; J. S. Mandeep; N. Misran (The Scientific World Journal)
This paper presents a printed wide-slot antenna design and prototyping on available low-cost polymer resin composite material fed by a microstrip line with a rotated square slot for bandwidth enhancement and defected ground structure for gain enhancement. An I-shaped microstrip line is used to excite the square slot. The rotated square slot is embedded in the middle of the ground plane, and its diagonal points are implanted in the middle of the strip line and ground plane. To increase the gain, four L-shaped slots are etched in the ground plane. The measured results show that the proposed structure retains a wide impedance bandwidth of 88.07%, which is 20% better than the reference antenna. The average gain is also increased, which is about 4.17 dBi with a stable radiation pattern in the entire operating band. Moreover, radiation efficiency, input impedance, current distribution, axial ratio, and parametric studies of S11 for different design parameters are also investigated using the finite element method-based simulation software HFSS.